THE INFLUENCE OF WORK MOTIVATION, WORK DISCIPLINE AND ORGANIZATIONAL CULTURE ON PERFORMANCE EMPLOYEES OF PT PUPUK ISKANDAR MUDA KRUENG GEUKUEH, DISTRICT NORTH ACEH - Nurkhaliza; Khairawati; Faisal Matriadi; Likdanawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study examines the influence of work motivation, work discipline, and organizational culture on the performance of employees of PT Pupuk Iskandar Muda (PIM) Krueng Geukueh, North Aceh. The decline in ammonia production in 2023 is the background of this study, which is thought to be influenced by low employee motivation and work discipline. The results of observations show dissatisfaction related to the lack of recognition of achievements, low time discipline and regulations, and incompatibility with organizational culture. the purpose of this study is to see the effect of work motivation, work discipline, and organizational culture on the performance of employees of PT Pupuk Iskandar Muda (PIM) Krueng Geukueh, North Aceh. The research method uses multiple linear regression analysis and also hypothesis testing using SPSS. the results of this study indicate that work motivation, work discipline, and organizational culture have a positive and significant effect on employee performance. Work motivation provided by superiors at PT Pupuk Iskandar Muda is proven to encourage employees to improve their performance. In addition, the implementation of good work discipline shows a significant contribution to employee performance, where discipline at work increases work effectiveness. Last but not least, a strong and positive organizational culture plays a major role in creating an environment that supports improved employee performance. The implication in this study is that increasing work motivation, work discipline, and organizational culture at PT Pupuk Iskandar Muda (PIM) can improve employee performance. Companies need to focus on strengthening motivation through rewards and recognition, consistent application of work discipline, and the development of a positive organizational culture to create an environment that supports work productivity and efficiency.